(untitled) (Community Based Medical Journal, 2023)
Multiple myeloma (MM) is a type of cancer occurs due to malignant plasma cell that affects with various clinical manifestations including renal impairment, anemia, bone disease and infection. The most common renal presentation of multiple myeloma is myeloma cast nephropathy. We described a case of multiple myeloma along with renal impairment in a 62-year old male patient. His serum B2-Microglobulin was 19.18 mg/L, which is much higher than reference value. His serum creatinine was 2.58 mg/dL. After continuing medication, the patient’s renal function was restored. This case is being reported for clinical knowledge dissemination and building clinical insight. CBMJ 2023 January: Vol. 12 No. 01 P: 111-114